(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
As the work for managing a whole LAN effectively withoutlimited purposes, there are works of Policy-based networkmanagement (PBNM). The existing PBNM is defined in someorganizations including the Internet Engineering Task Force(IETF). However, it has structural problems. For example,communications sent from many clients concentrate on acommunication control mechanism called PEP (PolicyEnforcement Point). To improve the problems, we have beenstudying next generation PBNM called Destination AddressingControl System (DACS) Scheme. The DACS Scheme controlsthe whole LAN through communication control by the clientsoftware as PEP which locates on a client computer. We havebeen studied on the aspect of principle until now. In thisresearch, we implement a DACS system to realize a concept ofthe DACS Scheme, and show implement method and results offunctional experiments.